SME Bank Financing, from a European Perspective - Karen van der Wiel; Andrei Dubovik; Fien van Solinge (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
Bank loans continue to be the main source of external financing for small and medium-sized enterprises (SMEs), in both the Netherlands and other European countries. Businesses are using those loans for expansion, innovation or as working capital.~ But Dutch SMEs are applying for fewer bank loans, and those applications are often rejected by the banks. How does SME bank financing in the Netherlands relate to other European countries, and what are the reasons for the differences?
Keywords: 330